Violence Against Women and Girls : Finance and Enterprise Development Brief - Gennari, Floriza; Arango, Diana; Hidalgo. Nidia (World Bank, Washington, DC, 2015)
Violence against women and girls (VAWG) affects survivorsapos; ability to achieve individual potential and contribute to the economy. Unequal gender norms within a household can limit a woman s control over and access to economic resources. Restraining womenapos;s ability to access economic resources is a form of intimidation and coercion. Although microfinance projects can reduce household vulnerability, merely offering resources to women does not enable and empower them to exert control over those resources or make decisions about their lives. Providing women with an income can contribute to disrupting household and gender dynamics, potentially contributing to VAWG.